The nomenclature of diplomatic agents as a source on the history of the English diplomatic corps of Henry VII - Mazarchuk, Dmitry V (Journal of the Belarusian State University. History, 2022)
The results of the analysis of the use of diplomatic nomenclature during the reign of Henry VII are presented. A total of 12 terms were identified, of which 5 were the most commonly used to refer to English ambassadors. The diplomatic nomenclature was poorly ordered, the terminology did not reflect the specific functional duties of the persons sent to the mission. The only exceptions were missions to receive cash payments due under an agreement with France. At the same time, the process of unification of the diplomatic nomenclature began, which was reflected in the use of stable formulas in the texts of ambassadorial powers of attorney. Based on the analysis of the diplomatic nomenclature, a conclusion was made about the fact that at the turn of the 15th–16th centuries ambassador hierarchy.